Sandton: a linguistic ethnography of small stories in a site of luxury - Kelleher, William (My University, 2018)
This is a linguistic ethnography that focuses on small stories (Bamberg and Georgakopoulou 2008, De Fina 2009, De Fina and Georgakopoulou 2015, Georgakopoulou 2006a and 2006b, 2008, 2014) within Bucholtz and Hall’s (2005) approach to identity and interaction. These two intersecting theoretical scaffoldings are completed by a geosemiotic approach (Scollon and Scollon 2003) to the discursive environment. The research therefore studies narrative interactions within communities of practice (Eckert and McConnell-Ginet 1992, 2007) across the spaces and fields of the research site of Sandton, Johannesburg; investigating both participant behaviour and discursive environment, in particular with respect to the semiotic landscape. It is a ‘new’ ethnography in that its aim is to better understand the new spaces of South Africa’s cities (Duff 2014). Methodologically the narrative interactions of participants are plotted onto the space of Sandton using GIS technology. This allows attention to be brought to the trajectories of participants and thus to change in interactive style, role and behaviour as participants enter, remain within and leave the site. Three principles of identity and interaction are explored and unpacked in depth for this linguistic ethnography: emergence, positionality and relationality. In addition to a focus on the site itself and its socio-historic processes, this thesis examines the trajectories across the space of the site, institutional discourse and practice through four emblematic companies and, finally, the ‘Born Free’ or ‘millenial’ participants. Through the different participants the research seeks to give an account of the subjectivities and understandings that will be relevant to the present, and future, of the site, and of the country. Axes of investigation are emergence of identity work, masculinity, religion, modernity, codeswitching, positionality with respect to macro, meso and micro discourses and interaction, and tactics of intersubjectivity (Bucholtz and Hall 2004b).
Thesis submitted for the degree of Doctor of Philosophy January 2018
Keywords: Ethnology--South Africa; Cities and towns